Bạn chưa đăng nhập. Vui lòng đăng nhập để hỏi bài

Những câu hỏi liên quan
asuna x kirito
Xem chi tiết
Lê Anh Tiến
Xem chi tiết
Nước Nam Người
Xem chi tiết
nono
6 tháng 9 2015 lúc 16:25

A=m3-m2+6m2-6m+9m-9

=m2(m-1)+6m(m-1)+9(m-1)

=(m-1)(m2+6m+9)=(m-1)(m+3)2

Chu Tuấn Kiệt
9 tháng 2 2016 lúc 17:59

(m+1)(m+3)2

Nguyễn Đức Thắng
25 tháng 2 2016 lúc 20:47

A=m3+5m2+3m-9

  =m2(m-1)+6m(m-1)+9(m-1)

  =(m-1)(m2+6m+9)

  =(m-1)(m+3)2

Duyên Nấm Lùn
Xem chi tiết
Phương An
15 tháng 9 2016 lúc 21:13

4a2b2 + 36a2b3 + 6ab4

= 2ab2(2a + 18ab + 3b2)

3n(m - 3) + 5m(m - 3)

= (3n + 5m)(m - 3)

2a(x - y) - (y - x)

= (x - y)(2a + 1)

4a2b3 - 6a3b2

= 2a2b2(2b - 3a)

Trương Quỳnh
Xem chi tiết
Bùi Thế Hào
26 tháng 3 2018 lúc 9:54

a3m+2a2m+am = am(a2m+2am+1) = am[(am)2+2am+1] = am(am+1)2

Phạm Tuấn Đạt
26 tháng 3 2018 lúc 10:01

Ta có :

a3m+2a2m+am 

= am(a2m+2am+1)

= am[(am)2+2am+1]

= am(am+1)2

_Guiltykamikk_
26 tháng 3 2018 lúc 12:33

\(a^{3m}+2a^{2m}+a^m\)

\(\Leftrightarrow a^m\left(a^{2m}+2a^m+1\right)\)

\(\Leftrightarrow a^m\left[\left(a^m\right)^2+2a^m+1\right]\)

\(\Leftrightarrow a^m\left(a^m+1\right)^2\)

\(\Leftrightarrow a^m\left(a^m+1\right)\left(a^m+1\right)\)

NGUYỄN duy tuấn
Xem chi tiết
Kaylee Trương
Xem chi tiết
Nguyễn Phạm Châu Anh
23 tháng 3 2017 lúc 15:21

\(3m^2-2m-1\)

\(=3m^2-3m+m-1\)

\(=3m\left(m-1\right)+\left(m-1\right)\)

\(=\left(m-1\right)\left(3m+1\right)\)

công chúa xinh xắn
23 tháng 3 2017 lúc 15:25

\(3m^2-2m-1\)

\(=3m^2+m-3m-1\)

\(=\left(3m^2+m\right)-\left(3m+1\right)\)

\(=m\left(3m+1\right)-\left(3m+1\right)\)

\(=\left(m-1\right)\left(3m+1\right)\)

Nguyễn Hồng Sơn
Xem chi tiết
khoinguyen phan
Xem chi tiết